THE DRIVING FORCES OF VOLITIONAL QUALITIES - Fariz Aydin (International Journal of Innovative Technologies in Social Science, 2022)
We know that historically, every nation connects its ideas for a happy future, first of all, with the younger generation. Proper upbringing of the young generation is one of the most important and urgent issues for any country. Also, in all countries of the world, young people are one of the main driving forces of socio-economic development, the driving force behind the reforms of society and at the same time the successor of the older generation. Being the most dynamic group in the society, young people take an active part in the socio-political, socio-economic and cultural life and stand at the center of all issues in the country. Generations are changing, countries are developing. However, traditions and national values, upbringing of the young generation in the spirit of patriotism are the key to the well-being of the people and the prosperity of the country to which it belongs. It should be noted that today the proper upbringing of the younger generation is important for the future of the country. In our research, great preference was given to young people. What is the first will in research? What are volitional qualities? We tried to answer questions such as. We talked in detail about the will, voluntary work, as well as the positive and negative volitional qualities formed mainly in young people. At the same time, we considered the role of volitional qualities in human activity, its impact on living conditions, the factors and motives that affect the formation of these qualities. In general, the research focused on national heroes, their volitional qualities and the impact of these qualities on the formation of young people. During the research conducted in accordance with the relevance of the topic, experimental psychological tests and questionnaires were conducted among a certain group of young people.